BELARUSIAN BIBLIOLOGY AND NATIONAL REVIVAL IN 1920s - DOVNAR, LARISA (Knygotyra, 2015)
Setting oneself the determination of the Belarusian bibliology development directions in the NATIONAL revival context as an object of the report and solving a problem of the definite reconstruction of the book knowledge in 1920s the author notes that the knowledge was one of the basic rests of the Belarusian national identification. Development of the Belarusian bibliology in the 1920s was connected closely with the second wave of the national revival in 1918–1929 (BSSR) and 1921–1939 (the Western Belarus). This period might be called the most fruitful period of the Belarusian nation development. Achievements of the short period surpass the whole 19th century. The first Belarusian bibliology significant achievements are connected with the first Belarusian scientific establishment “Inbelkult” (1922–1929) activities. The year of 1926 was full up the events when the solid two bibliological works were published: “400 years of Belarusian press, 1525–1925” and “Belarusian (Kryvian) book history” by Vatslav Lastovski. In the same year the Belarusian society of bibliophiles was established. The society first began to research a number of bibliological problems: Belarusian book culture, book press history, book art. A number of prominent scientists and Belarusian national revival figures paid great attention to bibliological problems. There were E. Karski, V. Picheta, B. Epimah-Shinila, M. Dovnar-Zapolski, V. Lastovski, A. Shliubski N. Shchekotichin, D. Dovgialo, S. Nekrashevich, M. Meleshko, N. Kasperovich, D. Zhelunovich, A. Stankevich. These figures were the pioneers in the field of Belarusian bibliology theory and history. After the State BSSR library opening the scientific-bibliographical and library science fields were started to be researched (I. Simanovski, J. Bibila). There was scientific discussion of Professional periodical press creation too. The study of local lore (“Nash krai”) and socio-literary (“Polymia”, “Uzvysha”) magazines as well as “The Inbelkult humanities department works» became the basic Belarusian bibliological tribune. However the Belarusian revival period was too short. In the end of the 1929s – in the beginning of the 1930s the Belarusian intellectuals tragedy took place. Many of them were called “natsdems” and prisoned or executed by the Soviet authorities. Right up to the beginning of the 1960s the Belarusian bibliology was in stagnation. The main lessons of the 1920s Belarusian bibliological heritage: in form: documental heritage is the most important constituent of national development; activities of special scientific and social centres are the powerful tools of the intellectual power concentration and progress in bibliological theory, methodology and history; professional bibliological printing is the essential tool of the knowledge development and dissemination; scientific staff training is the essential condition of successful bibiliological projects; in content: bibliological investigations became a section of historical, archival, study of local lore, philological, culturological complexes; the investigations basic directions are fixed: source study, historiography, preservation of memorials of book culture, book and book printing history, study of Skaryna, ancient book printing art, library science and bibliography, bibliophilia (ex-libristics), book culture; the research directions are defined: principles and criterions of national document identification; book typology, methods and methodology of bibliology. But the Belarusian book science achievements of the 1920s are very important. They shows the definite culture independence of Belarus.